Contribution of the P3AP2KB Service in Handling the Impact of Child Marriage in Sleman Regency - Rozak, Fakih Abdul; Putri Ayu Nurmalinda; Syarif Hidayatullah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2024)
The Religious Court is the final solution so that the marriage of a child can occur through the mechanism of requesting a marriage dispensation. The impact of child marriage that often occurs but is rarely realized is baby blues. The decision to marry must be accompanied by the ability to adapt in handling stress and social pressure as well as pressure from the family that will definitely arise. The purpose of this research is to determine the handling of the impacts resulting from the granting of a marriage dispensation application at the Sleman Regency Religious Court. This research a qualitative method with a case study approach. Data was collected through an interview process and information came from the Sleman Regency Religious Court and the P3AP2KB service. The results of this research show several factors behind the application for marriage dispensation at the Sleman Regency Religious Court, such as: pregnancy out of wedlock, customs/ culture, avoiding adultery, promiscuity and economics. The impacts resulting from the marriage dispensation include: protection of children’s rights, negative stigma from society, health problems both physically and psychologically, and economic difficulties. This research aims to recommend to all levels of society to participate in socialization by providing guidance and counseling for couples who apply for marriage dispensation. Even though the Sleman Regency P3AP2KB service has succeeded in making various efforts to deal with the impacts that arise as a result of granting requests for marriage dispensation, the reasons why marriages occur are not something that can be permitted and tolerated on an ongoing basis. Marriage should be and mature with good physical and psychological readiness to support the birth of a family that is Sakinah, mawadah, warahmah, and the children’s rights in the fields of education, economic sufficiency and a good understanding of all their interests in a positive way.